2010
DOI: 10.1523/jneurosci.0107-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Neural Timing Is Linked to Speech Perception in Noise

Abstract: Understanding speech in background noise is challenging for every listener, including those with normal peripheral hearing. This difficulty is attributable in part to the disruptive effects of noise on neural synchrony, resulting in degraded representation of speech at cortical and subcortical levels as reflected by electrophysiological responses. These problems are especially pronounced in clinical populations such as children with learning impairments. Given the established effects of noise on evoked respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
170
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 171 publications
(183 citation statements)
references
References 41 publications
12
170
0
1
Order By: Relevance
“…This could account for the selective relationship between extent of past music training and response timing to the CV transition in speech but not the steady-state vowel. By priming the auditory system to encode sound according to informational saliency and acoustic complexity (Strait et al, 2009;Kraus and Chandrasekaran, 2010), increased neural resources could be devoted to the most relevant acoustic features of auditory scenes. In fact, this may account for the inconsistency in group effects for neural timing in response to speech presented in quiet versus speech presented in noise: whereas the group effect in noise was driven by the Moderate group having faster timing than the Little and None groups, in quiet this was driven by poorer timing in the Little group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This could account for the selective relationship between extent of past music training and response timing to the CV transition in speech but not the steady-state vowel. By priming the auditory system to encode sound according to informational saliency and acoustic complexity (Strait et al, 2009;Kraus and Chandrasekaran, 2010), increased neural resources could be devoted to the most relevant acoustic features of auditory scenes. In fact, this may account for the inconsistency in group effects for neural timing in response to speech presented in quiet versus speech presented in noise: whereas the group effect in noise was driven by the Moderate group having faster timing than the Little and None groups, in quiet this was driven by poorer timing in the Little group.…”
Section: Discussionmentioning
confidence: 99%
“…1). This subcortical electrophysiologic response is a variant of the auditory brainstem response that is elicited in response to complex sounds instead of simple clicks or tones and is generated by synchronous firing of midbrain nuclei, predominantly inferior colliculus (IC; for review, see Chandrasekaran and Kraus, 2010 This individual only reported that training stopped at a "very young" age.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations